Analyzing the Potential of ChatGPT to Support Learning for the Students of College of Vocational Studies of IPB University - Muzaqi, Anggito Rangkuti Bagas; Prastowiyono, Daffarizqy; Ramdhana, Muhammad Fathi; Barus, Irma Rasita Gloria; Fami, Amata (PPM Telkom University, 2024)
a